How do institutional investors trade - O'CONNELL, Paul G. J. (Institutional Knowledge at Singapore Management University, 2004)
Using a novel and detailed custody trades dataset, this paper analyzes the trading behavior of institutions. Extant studies have examined the effects of past performance on trading by retail investors, day traders, and futures floor traders. Yet very little work has been done on institutions. We find that unlike other investors, institutions take on more risk following an increase in net profit and loss. However, the responses to a gain and loss are highly asymmetric. Institutions aggressively reduce risk in the wake of losses, but only mildly increase risk in the wake of gains. This asymmetry is more pronounced for experienced and older funds. Further, the performance dependence varies over the calendar year, and manifests itself at the security but not at the portfolio level. We relate these findings to the behavioral theories of narrow framing, dynamic loss aversion, and overconfidence.